THE CONCEPT OF LITERACY IN PEDAGOGICAL ACTIVITIES PRODUCED WITHIN A COLLABORATIVE CONTINUING EDUCATION PROGRAM - Severo Trivisiol, Vanessa (Cadernos do IL, 2017)
The objective is to analyze to what extent the concept of literacy subsidizes the activities developed within a continuing education program. We consider literacy as a tool of teaching and learning which goes beyond being literate (STREET, 2003, p. 77-78). Procedures of analysis: 1) to identify the nature of the activities t; 2) to quantify the recurrence of the activities previously classified; 3) to analyze the rhetorical organization of the unit. The activities explore the concept of literacy as an opportunity for the students to acquire knowledge through the reflection and the connection of the text with their social context.